2016
DOI: 10.1590/s0100-736x2016000200004
|View full text |Cite
|
Sign up to set email alerts
|

Troponina C na detecção imuno-histoquímica de alterações regressivas precoces no miocárdio de ovinos naturalmente intoxicados por Amaranthus spinosus (Amaranthaceae)

Abstract: ABSTRACT.-Costa S.Z.R., Peixoto P.V., Brust L.A.C., d' Avila M.S., Santos A.M., Driemeier D., Nogueira V. A. & França T.N. 2016. [Troponin C in the immunohistochemistry detection of early regressive changes in sheep myocardium naturally poisoned by Amaranthus spinosus (Amaranthaceae).] Troponina C na detecção imuno-histoquímica de alterações regressivas precoces no miocárdio de ovinos naturalmente intoxicados por Amaranthus spinosus (Amaranthaceae). Pesquisa Veterinária Brasileira 36(2):83-89. Curso de Pós-Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
1
5
0
2
Order By: Relevance
“…There was an increase in eosinophilic cardiomyocytes confirmed by the loss of troponin from cardiac myocytes through IHC using human cTnC antibody. These findings corroborate those observed in dogs with CKD and heartworm disease (Carretón et al 2012(Carretón et al , D'avila et al 2016, sheep with acute and subacute nephrotoxic injury (Costa et al 2016), and cattle (Pavarini et al 2012, Bandinelli et al 2014 with cardiac injuries, which confirm the viability of this technique for these species. Regarding the extent of cardiac injury in cats, small foci of isolated necrosis or individual cardiomyocytes were observed, demonstrating that, even in advanced stages of CKD, cardiac lesions manifest differently in this species, which can be explained by the different pathophysiology and consequent clinical-pathological behavior of the feline species (Bagshaw et al 2013).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…There was an increase in eosinophilic cardiomyocytes confirmed by the loss of troponin from cardiac myocytes through IHC using human cTnC antibody. These findings corroborate those observed in dogs with CKD and heartworm disease (Carretón et al 2012(Carretón et al , D'avila et al 2016, sheep with acute and subacute nephrotoxic injury (Costa et al 2016), and cattle (Pavarini et al 2012, Bandinelli et al 2014 with cardiac injuries, which confirm the viability of this technique for these species. Regarding the extent of cardiac injury in cats, small foci of isolated necrosis or individual cardiomyocytes were observed, demonstrating that, even in advanced stages of CKD, cardiac lesions manifest differently in this species, which can be explained by the different pathophysiology and consequent clinical-pathological behavior of the feline species (Bagshaw et al 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Few studies have reported the use of IHC with anti-troponin antibody to detect cardiac lesions in veterinary medicine. Recently, through IHC for the human cTnC antibody, degenerative-necrotic lesions have been observed in the heart of cattle poisoned by Amorimia exotropica (Pavarini et al 2012, Bandinelli et al 2014) and of sheep poisoned by Amaranthus spinosus (Costa et al 2016). Foci of hypereosinophilic cardiomyocytes with coagulation necrosis, neutrophilic inflammation, and subtle to mild variation in the staining pattern of some fibers with part of them showing a total loss of troponin I were found in the myocardium of dogs infected with Dirofilaria immitis (Carretón et al 2012(Carretón et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A diminuição ou ausência da expressão de troponina cardíaca observada em todos os bovinos e ovinos desse estudo, indica variável grau de lesão de cardiomiócitos. Recentemente, lesões degenerativo-necróti-cas semelhantes foram demonstradas através da imuno--histoquímica para cTnC no coração de bovinos intoxicados por Amorimia exotropica (Pavarini et al 2012, Bandinelli et al 2014) e ovinos por Amaranthus spinosus (Costa et al 2014). Além disso, estudos anteriores relatam o aumento da eosinofilia citoplasmática de fibras cardíacas em bovinos intoxicados por Mascagnia (Amorimia) sp.…”
Section: Discussionunclassified
“…Em ovinos, a troponina sérica foi dosada em casos de arritmia cardíaca após intoxicação por salinomicina (Hajimohammadi et al 2014) e lesão miocárdica em animais com acidose lática ruminal (Kirbas et al 2014). Com relação à imuno-histoquímica, são escassos os trabalhos que relatam o uso do anticorpo anti-cTnC na detecção de alterações cardíacas em bovinos (Tunca et al 2008, Pavarini et al 2012) e ovinos (Costa et al 2014). O anticorpo anticTnC humano é sensível para detectar lesões cardíacas em bovinos (Pavarini et al 2012) e ovinos (Costa et al 2014), o que sugere que os sítios antigênicos para estas proteínas são similares entre as espécies testadas.…”
Section: Discussionunclassified